Singularity [compact disc] - Hopkins, Jon (Domino Recording Co., 2018)
"Singularity marks the fifth album from the UK electronic producer and composer and the follow up to 2013's Mercury Prize nominated Immunity. Where Immunity charted the dark alternative reality of an epic night out, Singularity explores the dissonance between dystopian urbanity and the green forest. It is a journey that returns to where it began - from the opening note of foreboding to the final sound of acceptance. Shaped by his experiences with meditation and trance states, the album flows seamlessly from rugged techno to transcendent choral music, from solo acoustic piano to psychedelic ambient."--Amazon.com.